Understanding the Mechanisms through Which Adverse Childhood Experiences Affect Lifetime Economic Outcomes - Stefanie Schurer; Kristian Trajkovski (Institute of Labor Economics (IZA), 2018)
Over the past two decades, researchers have shown a growing interest in the role of adverse childhood experiences (ACEs) – children's confrontation with maltreatment and household dysfunction – in shaping lifetime opportunities. However, this is the first study to quantify the economic penalties of ACEs and identify the mechanisms which produce the relationship. We source data from the National Child Development Study to construct an ACE index based on prospective childhood information and estimate an earnings penalty of 7.3 percent for each additional ACE, a 53.1 percent higher probability of being welfare dependent, and a 34 percent higher probability of poverty at age 55, controlling for important background factors measured in childhood. The results are driven by parental neglect, a component of the ACE index based on teacher assessments. Observed differences in later-life earnings between children with and without neglect exposure can be fully explained by observable differences in human capital accumulated by age 33. The productivity loss in an economy due to parental failures to nurture and protect their children is likely to be high. Our findings contribute to a wider discussion on the multidimensionality and expanding definitions of childhood poverty.
Keywords: I32; J12; 330; childhood poverty; adverse childhood experiences; economic outcomes; welfare dependence; human capital